2018
DOI: 10.1002/1438-390x.1001
|View full text |Cite
|
Sign up to set email alerts
|

Frog survival and population viability in an agricultural landscape with a drying climate

Abstract: Amphibians are the most threatened class of vertebrate in the world. Although a number of causes of the amphibian decline phenomenon are emerging, there is a need for robust demographic data to be able to monitor current and future threats such as climate change. Despite this, few studies on amphibians have the lifehistory data available to undertake these analyses and fewer still have looked at the challenges to population viability posed by fragmentation-a feature inherent in agricultural landscapes where th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…There is considerable uncertainty in survival probabilities of juvenile chorus frogs, a pattern that is observed for many amphibians [ 229 , 230 ]. The complexity of marking and recapturing metamorphic and juvenile anurans make estimating survival very difficult [ 225 ].…”
Section: Resultsmentioning
confidence: 99%
“…There is considerable uncertainty in survival probabilities of juvenile chorus frogs, a pattern that is observed for many amphibians [ 229 , 230 ]. The complexity of marking and recapturing metamorphic and juvenile anurans make estimating survival very difficult [ 225 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is expected that the disappearance of the ponds and / or the decrease of their quality narrows the habitat diversity for several species, forcing amphibians to breed in suboptimal – i.e. sink- habitats (Pulliam, 2014) and decreasing the population and metapopulation viability in changing climate (Davis, Lohr & Roberts, 2018). The nearest pond distance in our study as a proxy of pond connectivity showed a slight increase with the pond loss, but the overall distances even with the loss of temporary ponds (Table 1) remained within the movement range of most species (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In some contexts, population viability modeling and decision analysis provide valuable tools for projecting future populations states (Converse and Grant, 2019;Davis et al 2019). However, in many human-shaped landscapes these approaches may have limited practical applicability, particularly where natural and cultural values are threatened by various economic interests and conflicts between stakeholders regarding nature conservation goals are common (Hartel et al 2019).…”
Section: Understand Socio-economic Drivers That Shape the Future Of Amentioning
confidence: 99%